Observations on Coastal Fishery of Okhamandal in Gujarat State - P., Gopalakrishnan (Fishery Technology, 2025)
The characteristics of coastal fishery of Okhamandal in Gujarat State are described. About 24000 fishermen, majority of them seasonal migrants from other places, produced on average of 36234 t of seafood every year valued at Rs. 44.6 crores. Over 1900 fishing vessels including trawlers and gill netters are seasonally in operation in this region. The landings consisted of crustaceans (12%), molluscans (2.7%) quality fish (29.4%), trash fish unsuitable for human consumption (45.4%) along with miscellaneous varieties. A capital investment of Rs. 72 crores and annual working capital of Rs. 25 crores were involved in the fishery. lnfrastructural facilities for landing, berthing and dry docking of fishing vessels, storage, preservation and processing of catch, accommodation of fishermen, education of fisherchildren, medical care, sanita tion were found to be inadequate whereas civic amenities like the munidpal drinking water supply and electric power were absent. The fishery economy was controlled by about 250 merchants who contracted 70% of production by hypothecation against monetary advances to boat owners. The average net annual earnings of an owner hypothecating the catch to merchant ranged between 0.5 to 0.53 lakhs while the merchant eamed between Rs. 0.3 to Rs. 0.4 lakh per boat. The majority of fisherfolk working as crew and shore labour (92%) eamed annually between Rs. 0.12 to 0.24 lakhs in respect of crew and Rs. 0.05 to Rs. 0.03 in case of women and children doing shore labour